Human amniotic fluid stem cells have better potential in early second trimester of pregnancy and can be reprogramed to iPS - S.W. Steven Shaw; Po-Jen Cheng; Yao-Lung Chang; An-Shine Chao; Tzu-Hao Wang; Shuenn-Dyh Chang; T'sang-T'ang Hsieh; Kuo-Hsuan Chang (Elsevier, 2017)
Objective: To study the difference of amniotic fluid stem cell potential at different gestational age. Materials and methods: Second trimester amniocentesis was performed during 15 to 22nd week of gestational age in a single medical center from 2015 to 2016. Early second trimester amniotic fluid stem cells (E-AFS) and later one (L-AFS) were defined 15-18th week, and 19-22nd week, respectively. Cell characteristics, surface markers and ability to form induced pluripotent stem cells (iPS) were studied. Results: All the amniotic fluid stem cells samples could be isolated and cultured from second trimester amniocentesis. E-AFS showed more Ckit + cell, shorted doubling time, smaller cell size and higher cell density compared to L-AFS. Both groups had the same stem cell surface markers with highly expression of CD44, CD73, CD90, and CD105, negative for CD45. They can easily be reprogramed into amniotic fluid stem cell derived iPS via standard induction. Conclusion: Human amniotic fluid stem cells could be isolated from early or late second trimester amniocentesis with the similar stem cell surface markers presentation, especially in mesenchymal stem cells markers. However, the cells from early second trimester amniocentesis have more Ckit + number and more potential characteristics compared to late second trimester amniocentesis. Both E-AFS and L-AFS could form the iPS easily which lead to the future disease modeling study.